Structural Gender Inequalities and Symptoms of Postpartum Depression in 40 Countries - Magana-Frade, I (Elsevier B.V., 2022)
Background: The role of structural gender inequality in macro-level differences in women s perinatal mental health remains largely unexplored. This short communication explores structural gender inequalities and their potential as a macro-level, upstream social determinant of postpartum depression (PPD). Methods: We compiled meta-analytically derived national-level prevalence estimates of PPD symptoms – based on the Edinburgh Postnatal Depression Scale – with economic (e.g., income inequality), health (e.g., infant mortality rate), sociodemographic (e.g., urban population), and structural gender inequality variables (e.g., abortion policies) for 40 countries. Meta-regression techniques and traditional p-value based stepwise procedures, complemented with a Bayesian model averaging approach, were used for a robust selection of variables associated with national-level PPD symptom prevalence. Results: Income inequality (β = 0.04, 95% CI = 0.02 to 0.07) and abortion policies (β = 0.02, 95% CI = 0.00 to 0.03) were the only variables selected in the final, adjusted model, accounting for 60.7% of cross-national variations in PPD symptoms. Limitations: Study quality of primary studies was not assessed and some national-level meta-analytical estimates were based on few primary studies. A fifth of world countries and territories could be included, with high-income regions overrepresented. High rate of missing national-level data for potential predictors of PPD. Cross-sectional analyses precludes causal inferences. Conclusions: Abortion policies are a significant macro-level social determinant of PPD, and its liberalization might be associated with women s mental health at a population level. Our findings should be a relevant argument for clinicians to advocate for changing discriminatory social norms against women. © 2021